PKM PEMBAGIAN BANTUAN LANGSUNG TUNAI DALAM MENJAGA KETAHANAN PANGAN DAN PENINGKATAN GIJI KELUARGA - Tasya Shiffa Firdaussa; Veronica Anjani; Teza Nur Fitri; Ratih Febi Anggela; Jaka Wijaya Kusuma; Hamidah Hamidah (LPPM Universitas Bina Bangsa, 2022)
Community service is one of the important commitments made by diversity in the context of blending into society. The existence of academics in rural community development is also a benchmark for the existence of universities in establishing cooperation with rural communities. One form of PKM that is carried out is to build villages by assisting villages in the distribution of Direct Cash Assistance. Through the method of meeting to homes, PKM focuses on the important role of maintaining food security at the government and community levels. Food management is carried out by rural communities, not only as a learning discourse but also expected to be able to contribute to the community giving birth to new things in the field of food security and Nutrition Improvement